Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Pada PLN UP3 Sidoarjo - Nurul Nur Rohmawati Wulandari; Maharani Ikaningtyas (Jurnal Riset dan Inovasi Manajemen, 2024)
In an increasingly diversified business landscape, marketing strategies stand as a primary key to a company's success. This study delves into the marketing strategies of PLN UP3 Sidoarjo, specifically in boosting the sales volume of its electricity services. The research method employed is qualitative descriptive, involving in-depth interviews and analysis. The findings reveal a spectrum of marketing strategies encompassing product, price, promotion, and distribution/placement. Implemented marketing strategies such as service diversification, setting affordable tariffs, educational campaigns, and community partnerships have contributed to a stable increase in the number of customers. However, evaluating these strategies should extend beyond customer acquisition, also considering the increase in electricity consumption per customer. In conclusion, PLN UP3 Sidoarjo adopts a holistic approach that successfully enhances public awareness of its electricity services, augments the customer base, and improves customer service.